Pengenalan PHP Sebagai Dasar Pemrograman Web di SMA Islam Bahrul Ulum: Penelitian - Muhammad Yunus Rangkuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to introduce PHP as a basic web programming language for students of SMA Islam Bahrul Ulum, Tangerang Selatan. The research adopts a participatory approach involving 30 students in grade XI. Using project-based learning and hands-on practice, students were guided to understand basic syntax, logic, and dynamic web concepts using PHP and XAMPP. The results show a 56% improvement in understanding web programming. This study concludes that early exposure to coding increases students’ digital literacy, logical thinking, and interest in technology-related careers.